Development of Problem-Based Health Education Media to Improve Students' Reasoning and Physics Concepts Mastery - Siregar, Abdul Hakim; Srijayanti, Putri (Jurnal Pendidikan MIPA, 2022)
Health education is the main focus in fostering students. This is a fundamental part of starting a healthy life in an educational environment. This study aims to develop a valid and effective problem-based health physics learning tool. The object of the research was FIK students who took the Health Education course as many as 49 students of Class A as the experimental class and 39 students of Class B as the control class. The method used is Research and Development with a pretest-posttest control group design. The results showed that the problem-based health physics learning device that had been tested by three experts was feasible to be applied in classroom learning. The N-gain of the experimental class students' reasoning was 0.6 and the control class was 0.3, while the N-gain of the experimental class students' conceptual mastery was 0.55 and the control class was 0.43. Furthermore, it can be concluded that the use of problem-based health physics learning tools is effective for improving students' reasoning and mastery of conceptsKeywords: health education, reasoning physics concept, concept mastery.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1149-1157